Battery monomer, battery and electric device
Patent Information
- Application Number
- CN202380060956.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-17
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-04-17
AI Technical Summary
The existing battery cells have poor cycle performance, especially during the cycle charge and discharge process, they are prone to lack of liquid, which leads to increased polarization and shortened life.
Introduce liquid-absorbing polymers into the electrode plates of the battery cells, and use liquid-retaining polymers in the isolation membranes to optimize the structures of the electrode plates and isolation membranes to improve the electrolyte reabsorption rate and liquid retention capacity, and reduce Risk of fluid deficiency.
By improving the performance of the electrode plates and isolation membranes, the stability and cycle performance of the battery cells during cycling are improved, the battery life is extended, and polarization and liquid shortage are reduced.
Smart Images

Figure CN119731826A_ABST
Abstract
Description
Battery cells, batteries and electrical devices Technical Field
[0001] The present application relates to the field of batteries, and in particular to a battery cell, a battery, and an electrical device. Background Art
[0002] Battery cells have the characteristics of high capacity and long life, and are therefore widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric airplanes, electric boats, electric toy cars, electric toy boats, electric toy airplanes and power tools, etc.
[0003] As battery applications become increasingly widespread, the requirements for battery cell performance are becoming increasingly stringent. However, the current cycle performance of battery cells is relatively poor and still needs to be further improved.
[0004] Summary of the Invention
[0005] The embodiments of the present application are made in view of the above-mentioned problems, and an object thereof is to provide a battery cell, a battery, and an electric device.
[0006] A first aspect of the present application provides a battery cell, comprising an electrode assembly, the electrode assembly comprising an electrode plate and a separator; the electrode plate comprising a current collector and a film layer comprising an active material and a liquid-absorbing polymer disposed on at least one surface of the current collector, the electrode plate satisfying the following conditions: v / λ≥1.2; v represents the liquid absorption rate of the film layer, in units of mg / s; λ represents the porosity of the film layer; the separator comprising a liquid-retaining polymer, wherein the separator satisfies the following conditions:
[0007] Therefore, the electrode plates in the battery cell of the embodiment of the present application are provided with liquid-absorbing polymers, which help the electrode plates to reabsorb electrolyte, so that the electrolyte infiltrates the electrode plates more evenly and fully, thereby improving the stability of the battery cell during the cycle; the isolation membrane of the battery cell is provided with liquid-retaining polymers, and the isolation membrane has a strong liquid-retaining capacity. During the cyclic charge and discharge process of the battery cell, the electrolyte is not easily squeezed out, thereby reducing the liquid shortage during the cyclic charge and discharge process, reducing battery polarization, and improving the cycle performance of the battery cell.
[0008] In some embodiments, the active material includes a positive electrode active material, and the electrode plate satisfies the following conditions: 1.2≤v / λ≤4.50. When the electrode plate satisfies the above range, its liquid absorption rate is faster, which can increase the electrolyte reabsorption rate, thereby improving the cycle performance of the battery cell.
[0009] In some embodiments, the active material includes a negative electrode active material, and the electrode plate satisfies: 3≤v / λ<50.00. When the electrode plate meets the above range, its liquid absorption rate is faster, which can increase the electrolyte reabsorption rate, thereby improving the cycle performance of the battery cell.
[0010] In some embodiments, the isolation film satisfies:
[0011] Therefore, when the isolation membrane of the embodiment of the present application meets the above conditions, its liquid retention capacity can be further improved, which can further reduce the lack of liquid during the cyclic charge and discharge process, reduce battery polarization, and improve the cycle performance of the battery cell.
[0012] In some embodiments, the isolation film satisfies:
[0013] Therefore, when the isolation membrane of the embodiment of the present application meets the above conditions, its liquid retention capacity can be further improved, which can further reduce the lack of liquid during the cyclic charge and discharge process, reduce battery polarization, and improve the cycle performance of the battery cell.
[0014] In some embodiments, the isolation film satisfies:
[0015] Therefore, when the isolation membrane of the embodiment of the present application meets the above conditions, its liquid retention capacity can be further improved, which can further reduce the lack of liquid during the cyclic charge and discharge process, reduce battery polarization, and improve the cycle performance of the battery cell.
[0016] In some embodiments, the isolation membrane further includes a liquid-absorbing polymer; optionally, the unit volume mass of the liquid-absorbing polymer in the electrode plate is A1, and the unit volume mass of the liquid-absorbing polymer in the isolation membrane is A2, 1.0≤A1 / A2≤1.6; optionally, 1.2≤A1 / A2≤1.5.
[0017] In some embodiments, the electrode plate further includes a liquid-retaining polymer; optionally, the unit volume mass of the liquid-retaining polymer in the electrode plate is B1, and the unit volume mass of the liquid-retaining polymer in the isolation membrane is B2, 0.4≤B1 / B2≤0.9; optionally, 0.5≤B1 / B2≤0.8.
[0018] In some embodiments, the mass per unit volume of the liquid-absorbing polymer in the electrode plate is C1, the mass per unit volume of the liquid-retaining polymer in the isolation membrane is C2, and 0.1≤C1 / C2≤5.
[0019] In some embodiments, the liquid-retaining polymer comprises an ether polymer.
[0020] Optionally, the ether polymer includes a structural unit represented by formula (BI) and / or a structural unit represented by formula (BII),
[0021] In formula (BI), R 21 and R 22 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; R 23 Including substituted or unsubstituted C1-C5 alkylene;
[0022] In formula (BII), R 24 to R 27 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 alkoxy group or an ether group, and R 24 to R 27 At least one of them contains a substituted or unsubstituted C1-C3 alkoxy group or an ether group.
[0023] In some embodiments, the liquid retaining polymer comprises an ester polymer.
[0024] Optionally, the ester polymer is made into a sheet structure; the sheet structure is (T m3 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K2, 1<K2<∞, T m3 ℃ represents the melting temperature of the ester polymer; optionally, 1<K2≤100; further optionally, 1<K2≤10.
[0025] In some embodiments, the ester polymer includes a structural unit represented by formula (CI) and / or a structural unit represented by formula (CII),
[0026] In formula (CI), R 31 、R 32 and R 33 Each independently includes a hydrogen atom, or a substituted or unsubstituted C1-C8 alkyl group; R 34 Including substituted or unsubstituted C1-C8 alkyl, or substituted or unsubstituted C1-C8 hydroxyalkyl;
[0027] In formula (CII), R 35 including substituted or unsubstituted C2-C6 methylene; optionally, R 35Each independently includes a substituted or unsubstituted C2-C4 methylene group.
[0028]
[0029] In some embodiments, the liquid retaining polymer comprises a fluorinated polymer.
[0030] Optionally, the crystallinity of the fluoropolymer measured by differential scanning calorimetry is Xc1, 0<Xc1≤30%; the melting temperature of the fluoropolymer is T m1 , its unit is ℃, 0<T m1 ≤140.
[0031] In some embodiments, the glass transition temperature of the fluorinated polymer is T g1 , its unit is ℃, -150≤T g1 ≤60.
[0032] In some embodiments, the fluorinated polymer comprises at least one of the structural units represented by formula (AI) to the structural units represented by formula (AIII),
[0033] In formula (AI) and formula (AII), R 11 、R 12 、R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a bromine atom, a substituted or unsubstituted C1-C3 alkyl group or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 、R 12 、R 13 and R 14 At least one of them contains a fluorine atom;
[0034] In formula (AIII),
[0035] R 15 including a single bond, a substituted or unsubstituted C1-C3 alkyl group; p is a positive integer selected from 1 to 3; and n is a positive integer selected from 1,000 to 30,000.
[0036] In some embodiments, the liquid-retaining polymer further comprises an ether polymer, wherein the ether polymer is made into a sheet structure; the sheet structure is (T m2 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K1, 1<K1<∞, T m2 ℃ represents the melting temperature of the ether polymer; optionally, 1<K1≤100; further optionally, 1<K1≤10.
[0037] In some embodiments, the liquid retaining polymer comprises an aldehyde-ketone polymer.
[0038] Optionally, the aldehyde-ketone polymer is made into a sheet structure; the sheet structure is (T m4 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K3, 0.8≤K3<∞, T m4 ℃ represents the melting temperature of the aldehyde-ketone polymer; optionally, 0.8≤K3≤100; further optionally, 0.8≤K3≤10.
[0039] In some embodiments, the aldehyde-ketone polymer comprises a structural unit represented by formula (DI) and / or a structural unit represented by formula (DII),
[0040] In formula (DI), R 41 Including single bonds, substituted or unsubstituted C1-C6 methylene; R 42 including hydrogen atoms, substituted or unsubstituted C1-C6 alkyl groups;
[0041] In formula (DII), R 43 to R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from an integer from 0 to 5, and at least one of r and s is selected from a positive integer.
[0042] In some embodiments, the isolation body includes a substrate, and the polymer layer is disposed on at least one surface of the substrate.
[0043] In some embodiments, the isolation membrane includes a porous substrate, and the liquid-retaining polymer is distributed in the pores of the porous substrate.
[0044] In some embodiments, the isolation membrane includes a porous substrate and a polymer layer disposed on at least one surface of the porous substrate, wherein the polymer layer includes the liquid-retaining polymer.
[0045] In some embodiments, the coating weight of the liquid-retaining polymer is 0.5 mg / 1540.25 mm2 to 5 mg / 1540.25 mm2. When the coating weight is within the above range, the liquid-retaining capacity of the separator can be further improved.
[0046] In a second aspect, the present application proposes a battery comprising a battery cell as described in any embodiment of the first aspect of the present application.
[0047] In a third aspect, the present application proposes an electrical device comprising a battery as described in any embodiment of the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0049] FIG1 is a schematic diagram of a battery cell according to an embodiment of the present application.
[0050] FIG. 2 is an exploded schematic diagram of an embodiment of the battery cell of FIG. 1 .
[0051] FIG3 is a schematic diagram of an embodiment of a battery module of the present application.
[0052] FIG4 is a schematic diagram of an embodiment of a battery pack of the present application.
[0053] FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 .
[0054] FIG6 is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.
[0055] The drawings are not necessarily drawn to scale.
[0056] The following are the descriptions of the reference numerals:
[0057] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module;
[0058] 5. Battery cell; 51. Housing; 52. Electrode assembly;
[0059] 53. Cover plate;
[0060] 6. Electrical equipment. DETAILED DESCRIPTION
[0061] The following detailed description specifically discloses the embodiments of the battery cells, batteries, and electrical devices of the present application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0062] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0063] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. Unless otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0064] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may further include step (c), which indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.
[0065] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may indicate that other components not listed may also be included or that only the listed components are included.
[0066] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0067] In this application, the terms "plurality" and "multiple" refer to two or more.
[0068] The term "alkyl" encompasses both straight and branched chain alkyl groups. For example, the alkyl group may be a C1-C5 alkyl group, a C1-C4 alkyl group, a C1-C3 alkyl group, or a C1-C2 alkyl group. In some embodiments, the alkyl group includes a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, and the like. Additionally, the alkyl group may be optionally substituted. When substituted, the substituent includes a fluorine atom.
[0069] The term "alkoxy" refers to a group in which an alkyl group is connected to an oxygen atom by a single bond. For example, the alkoxy group can be a C1 to C5 alkoxy group, a C1 to C3 alkoxy group, or a C1 to C2 alkoxy group. In some embodiments, the alkoxy group can include a methoxy group, an ethoxy group, or a propoxy group. In addition, the alkoxy group can be optionally substituted.
[0070] The term "halogen atom" refers to a fluorine atom, a chlorine atom, a bromine atom or the like.
[0071] The term "hydrogen" refers to 1H (protium, H), 2H (deuterium, D), or 3H (tritium, T). In various embodiments, "hydrogen" may be 1H (protium, H).
[0072] A battery cell consists of a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. The separator is located between the positive and negative electrode sheets to isolate them from each other. During the charge and discharge cycles of a battery cell, the electrode assembly expands in volume. This expansion force is particularly high in the later stages of a battery cell cycle, causing the electrolyte to be squeezed out and making electrolyte reabsorption difficult. This increases the risk of electrode shortfalls and bridge failure, potentially deteriorating the battery cell's cycling performance and shortening its cycle life.
[0073] In view of the above problems, the embodiment of the present application proposes a battery cell, in which the electrode plates in the battery cell are provided with liquid-absorbing polymers, which help the electrode plates to reabsorb electrolyte, so that the electrolyte infiltrates the electrode plates more evenly and fully, thereby improving the stability of the battery cell during the cycle; the isolation membrane of the battery cell is provided with a liquid-retaining polymer, and the isolation membrane has a strong liquid-retaining capacity. During the cyclic charge and discharge process of the battery cell, the electrolyte is not easily squeezed out, thereby reducing the liquid shortage during the cyclic charge and discharge process, reducing battery polarization, and improving the cycle performance of the battery cell.
[0074] battery cells
[0075] In a first aspect, an embodiment of the present application provides a battery cell, comprising an electrode assembly, wherein the electrode assembly comprises an electrode sheet and a separator;
[0076] The electrode plate comprises a current collector and a film layer containing an active substance and a liquid-absorbing polymer disposed on at least one surface of the current collector, and the electrode plate satisfies: v / λ≥1.20;
[0077] v represents the liquid absorption rate of the film layer, and its unit is mg / s;
[0078] λ represents the porosity of the membrane layer;
[0079] The isolation film includes a liquid-retaining polymer, and the isolation film satisfies:
[0080] M represents the mass of the separator that does not absorb the electrolyte, and its unit is g;
[0081] m1 represents the mass of the separator measured at ambient pressure after being immersed in the electrolyte for 2 hours, and its unit is g;
[0082] m2 represents the mass of the isolation membrane weighed at a pressure of 10000 N in ambient pressure after the isolation membrane has been immersed in the electrolyte for 2 hours, and its unit is g.
[0083] When the above formula is used for specific calculations, only the specific values are taken into account, without taking into account the units of the parameters.
[0084] The electrode plates in the battery cell of the embodiment of the present application are provided with liquid-absorbing polymers, which help the electrode plates to reabsorb electrolyte, so that the electrolyte infiltrates the electrode plates more evenly and fully, thereby improving the stability of the battery cell during the cycle; the isolation membrane of the battery cell is provided with a liquid-retaining polymer, and the isolation membrane has a strong liquid-retaining ability. During the cyclic charge and discharge process of the battery cell, the electrolyte is not easily squeezed out, thereby reducing the liquid shortage during the cyclic charge and discharge process, reducing battery polarization, and improving the cycle performance of the battery cell.
[0085] In this application, the method for detecting the liquid absorption rate of the electrode comprises the following steps:
[0086] A predetermined amount of electrolyte is drawn by a capillary tube;
[0087] The capillary is brought into contact with the electrode plate, and the electrode plate to be tested absorbs the electrolyte in the capillary under capillary action;
[0088] After a predetermined time t, the liquid level h of the electrolyte absorbed in the capillary is recorded, and the amount of electrolyte absorbed is calculated based on the liquid level h and diameter d of the capillary and the density ρ of the electrolyte. The liquid absorption rate v of the electrode plate is quantitatively calculated based on the ratio of the absorbed amount and the predetermined time t.
[0089] Exemplarily, d takes a value of 0.2 to 1, for example, a value of 0.2; h takes a value of 3 to 5, for example, a value of 3.
[0090] The capillary tube has capillary channels that allow it to directly absorb electrolyte through capillary action, without the need for an external drive unit to provide suction power. This allows, on the one hand, more precise control of the amount of electrolyte absorbed through capillary action; on the other hand, because the electrode plate absorbs electrolyte through its own capillary action, the electrode plate only draws electrolyte from the capillary tube when the capillary tube contacts the electrode plate to be tested. When the contact is broken, the electrolyte in the capillary tube stops flowing out. Therefore, the amount of electrolyte absorbed in the capillary tube can accurately reflect the amount of electrolyte absorbed by the electrode plate, further improving the accuracy of the test results and achieving quantitative calculation of the electrolyte absorption rate of the electrode plate.
[0091] This application uses standard electrolyte as the test sample for testing. The specific formula of the electrolyte can refer to the electrolyte formula in the examples.
[0092] The liquid-absorbing polymer of the present application is introduced during the film preparation process, which can form uniform high wetting points in the film, increase the overall liquid absorption speed of the film, and thus improve the cycle performance of the battery cell.
[0093] In the embodiment of the present application, the porosity of the membrane layer in the electrode plate is the ratio of the pore volume in the membrane layer to the overall volume of the membrane layer, and can be detected using equipment and methods known in the art, for example, according to GB / T21650.2-2008 "Determination of pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method Part 2: Analysis of mesopores and macropores by gas adsorption method" and ASTMD2873-94el "Standard Test Method for Interior Porosity of Poly(Vinyl Choride)(PVC)Resins by Mercury Intrusion Porosimetry".
[0094] Alternatively, the porosity of the membrane layer can be calculated using the formula (1-P1 / P2);
[0095] P1 represents the actual compacted density of the film layer, and its unit is g / cm 3The actual compaction density P1 refers to the ratio of the mass of the active material layer per unit area in the electrode plate to its thickness. The actual compaction density is determined by the force of the roller pressing after the electrode plate is coated. The unit is g / cm 3 The specific test steps are to take an electrode sheet of a certain area S, weigh the mass M of its active material layer, and measure the thickness D of the film layer. The actual compaction density = M / (S×D).
[0096] P2 represents the actual compacted density of the active material, and its unit is g / cm 3 ; The true compacted density P2 refers to the density of the active material itself in the active material layer.
[0097] The active material is a negative electrode active material such as graphite. The density of graphite is 2.25 g / cm 3 The actual compacted density of the active material is 2.25 g / cm 3 .
[0098] The active material is used as the positive electrode active material for explanation. Specifically, the true compacted density refers to the mass per unit "actual volume of solid material (excluding open and closed pores and pores between particles)" in a dense state. The true volume V is obtained by testing, and then the true compacted density is calculated according to P = m / V. The test can be carried out in accordance with GB / T24586-2009. Specifically, the test steps are as follows:
[0099] 1) Pretreatment: Place a clean and dry sample cup on a balance, reset it to zero, add the powder sample to the cup, filling it to about 1 / 2 of the cup volume, and record the sample mass.
[0100] 2) Place the sample cup containing the sample in the true density tester, seal the test system, and introduce helium according to the program. By detecting the pressure of the gas in the sample chamber and expansion chamber, the true volume is calculated according to Bohr's law (PV=nRT), and thus the true compacted density is calculated.
[0101] The separator can be made from a substrate and a liquid-retaining polymer. Alternatively, the separator can be derived from a battery cell. The battery cell is disassembled, and the separator soaked in electrolyte is removed from the battery cell. The separator is then rinsed with deionized water and vacuum-dried at 80°C for 12 hours to obtain the separator. This separator can then be used for separator tests such as mass, liquid absorption rate, and porosity.
[0102] M represents the mass of the separator that has not absorbed the electrolyte, which can also be understood as the mass of the separator itself. Specifically, the separator can be cut into 10 pieces of 1540.25mm 2 The mass of the disc is weighed on an electronic balance.
[0103] m1 represents the mass of the separator after being immersed in the electrolyte for 2 hours and weighed at ambient pressure. Specifically, the separator can be cut into 10 pieces of 1540.25 mm 2 After immersing the disc in the electrolyte for 2 hours, take out the disc and weigh it after hanging it in the air for 2 minutes under ambient pressure.
[0104] m2 represents the mass of the separator after it is immersed in the electrolyte for 2 hours and then weighed under a force of 10000N in ambient pressure. Specifically, the separator can be cut into 10 pieces of 1540.25mm 2 After immersing the disc in the electrolyte for 2 hours, the disc is taken out, stacked in sequence, and a force of 10000N is applied under ambient pressure, and the mass of the isolation membrane is weighed.
[0105] This application is tested using a standard electrolyte as a test sample. The specific formula of the electrolyte can refer to the electrolyte formula in the embodiment. For example, the electrolyte includes ethylene carbonate EC, ethyl methyl carbonate EMC, and dimethyl carbonate DMC in a volume ratio of 1:1:1, and the electrolyte also includes lithium hexafluorophosphate LiPF6 with a molar concentration of 1 mol / L.
[0106] It can be defined as the liquid retention capacity Λ.
[0107] The isolation membrane of the embodiment of the present application includes a liquid-retaining polymer. The isolation membrane includes a liquid-retaining polymer. The isolation membrane has a strong liquid-retaining ability. During the cyclic charge and discharge process of the battery cell, the electrolyte is not easily squeezed out, which reduces the liquid shortage during the cyclic charge and discharge process, reduces battery polarization, and improves the cycle performance of the battery cell.
[0108] Optionally,
[0109] When the separator meets the above conditions, the separator has a strong liquid retention capacity, which can reduce the lack of liquid during the cyclic charge and discharge process, reduce battery polarization, and improve the cycle performance of the battery cell.
[0110] For example, It can be:
[0111] 25.1%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, 36%, 36.5%, 37%, 37.5%, 38%, 39 %, 40%, 41%, 42%, 45%, 46%, 48%, 50%, 52%, 55%, 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88%, 90%, 92%, 95%, 96%, 97%, 98%, 99% or a range consisting of any two of the above values.
[0112] In some embodiments, the isolation film satisfies:
[0113] m1-M represents the ratio of the amount of liquid absorbed by the isolation membrane to the mass of the isolation membrane itself, which can characterize the liquid absorption capacity of the isolation membrane, that is, the amount of electrolyte absorbed by the isolation membrane, and its liquid retention capacity can also be relatively improved.
[0114] It can be defined as the liquid retention rate of the isolation membrane.
[0115] When the separator meets the above conditions, the liquid absorption capacity of the separator is relatively good, which is beneficial to improving the absorption rate of the electrolyte, thereby further improving the cycle performance of the battery cell.
[0116] For example, It can be:
[0117] 80%, 85%, 88%, 90%, 92%, 95%, 96%, 97%, 98%, 99%, 100%, 105%, 110%, 120%, 130%, 140%, 150%, 160%, 170%, 180%, 190%, 200%, 210%, 220%, 230%, 240%, 250%, 260%, 270%, 280%, 290%, 300%, or a range consisting of any two of the above values.
[0118] In some embodiments, the isolation film satisfies:
[0119] (m2-M) / M represents the ratio of the amount of liquid retained by the isolation membrane under external action to the mass of the isolation membrane itself, which can characterize the liquid retention capacity of the isolation membrane.
[0120] It can be defined as the liquid retention rate after the isolation membrane is pressurized.
[0121] When the separator meets the above conditions, even if the separator is in a pressurized state, the separator has a relatively good liquid retention capacity, and the electrolyte adsorbed by the separator is not easily squeezed out, thereby increasing the migration rate of active ions and further improving the cycle performance of the battery cell.
[0122] For example, It can be:
[0123] 20.0%, 22.5%, 25.1%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, 36%, 36.5%, 37%, 37.5%, 38%, 39%, 40%, 41%, 42%, 45%, 46%, 48%, 50%, 52%, 55%, 60%, 62%, 65% %, 68%, 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88%, 90%, 92%, 95%, 96%, 97%, 98%, 99%, 100%, 105%, 110%, 120%, 130%, 140%, 150%, 160%, 170%, 180%, 190%, 200%, 210%, 220%, 230%, 240%, 250%, 260%, 270%, 280%, 290%, 300% or a range consisting of any two of the above values.
[0124] In some embodiments, the separator further comprises a liquid-absorbing polymer. The introduction of the liquid-absorbing polymer can improve the liquid-absorbing capacity of the separator, thereby increasing the rate at which the separator absorbs the electrolyte.
[0125] In some embodiments, the battery cell satisfies 0≤y / V 总孔 ≤15%;
[0126] y represents the volume of free electrolyte in the battery cell, in mL;
[0127] V 总孔 The value representing the pore volume of the electrode assembly, with the unit being mL.
[0128] When calculating a formula, only the numerical value is substituted for the calculation, without substituting the unit for the calculation.
[0129] When the battery cell meets the above conditions, the content of free electrolyte in the battery cell is extremely small, or even the battery cell basically contains no free electrolyte, which can significantly improve the reliability and cycle performance of the battery cell.
[0130] For example, y / V总孔 It can be 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, or a range consisting of any two of the above values. 总孔 A value of 0 indicates that the amount of free electrolyte is 0 mL, that is, there is basically no free electrolyte in the battery cell.
[0131] The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. The pore volume of the electrode assembly includes the sum of the pore volume of the positive electrode sheet, the pore volume of the negative electrode sheet, and the pore volume of the separator. In the embodiments of the present application, pore volume has a meaning commonly known in the art and can be measured using equipment and methods commonly known in the art. For example, it can be obtained by gas displacement. The pore volume is vm, where v represents the apparent volume (i.e., the total volume) and m represents the true volume.
[0132] In some embodiments, the battery cell further satisfies: 0≤y / Ah≤15%;
[0133] y represents the volume of free electrolyte in the battery cell, in mL;
[0134] Ah represents the value of the nominal capacity of the battery cell, and its unit is Ah.
[0135] When calculating a formula, only the numerical value is substituted into the formula without its unit.
[0136] The volume y (mL) of the free electrolyte can be measured by the following method: a fresh battery cell is fully charged to 0% SOC, a hole with a diameter of 5-8 mm is opened at a local position of the battery cell, and the battery cell is placed on top of a container with the hole facing downward and directly above the container, so that the free electrolyte inside the battery cell can drip into the container below. The battery cell is left to stand for 3 to 5 hours so that the free electrolyte inside can drip into the container, and then the volume of the electrolyte in the container is measured to obtain y. In the embodiment of the present application, the fresh battery cell can be a battery cell that has just left the factory (not subjected to charge and discharge cycles after formation), or a battery cell that is assembled on an electrical device and has been cycled less than 10 times.
[0137] When the battery cell meets the above conditions, the content of free electrolyte in the battery cell is extremely small, or even the battery cell basically contains no free electrolyte, which can significantly improve the reliability and cycle performance of the battery cell.
[0138] For example, y / Ah can be 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, or a range consisting of any two of the foregoing values. A y / Ah of 0 indicates zero free electrolyte, i.e., substantially no free electrolyte is present in the battery cell.
[0139] In some embodiments, after the battery cell is subjected to a linear frequency sweep vibration test, it is charged to 100% state of charge (SOC). A hole is opened on the battery cell, and the hole is located at the lowest point in the vertical direction. The volume of electrolyte flowing out of the battery cell is recorded as M1, where 0 mL ≤ M1 ≤ 0.5 mL. Optionally, M1 is 0 mL.
[0140] in,
[0141] The vibration direction of the linear sweep vibration test is: single vibration up and down;
[0142] The vibration frequency of the linear sweep vibration test is: 10Hz~55Hz;
[0143] The maximum acceleration of the linear sweep vibration test is: 30m / s 2 ;
[0144] The number of sweep cycles of the linear sweep vibration test is: 10 times;
[0145] The vibration time of the linear sweep frequency vibration test is 3 hours.
[0146] In the related art, during use, battery cells may vibrate under the action of external forces, and the electrolyte in the electrode assembly may separate from the electrode assembly under the action of vibration, forming free electrolyte. The free electrolyte in the battery cell may leak, causing corrosion to the battery cell and leading to risks such as battery cell failure. However, the embodiments of the present application can effectively gather and throw out the liquid electrolyte inside the battery cell by subjecting the battery cell to static and vibration treatment, thereby more accurately judging whether there is flowing liquid electrolyte between the battery cell shell and the electrode assembly, and determining the content of free electrolyte. When the battery cell of the embodiments of the present application meets the above conditions, the content of free electrolyte in the battery cell is extremely small, or even the battery cell basically contains no free electrolyte, which can significantly improve the reliability and cycle performance of the battery cell.
[0147] For example, M1 can be 0 mL, 0.05 mL, 0.1 mL, 0.15 mL, 0.2 mL, 0.25 mL, 0.3 mL, 0.35 mL, 0.4 mL, 0.45 mL, 0.5 mL, or a range consisting of any two of the foregoing values. M1 of 0 mL indicates zero free electrolyte, meaning that substantially no free electrolyte remains within the battery cell after the linear frequency sweep vibration test.
[0148] In some embodiments, after the battery cell undergoes the above-mentioned vibration test, the shell is removed, the electrode assembly is taken out and subjected to an extrusion test, and the volume of the electrolyte flowing out of the electrode assembly is recorded as M2 (the extrusion equipment is suspended, and a weighing balance and an electrolyte collection container are set at the bottom), 0 mL ≤ M2 ≤ 0.5 mL, optionally, M2 is 0 mL;
[0149] in,
[0150] The extrusion direction of the extrusion test is: perpendicular to the thickness direction of the electrode assembly 52;
[0151] The extrusion degree of the extrusion test is: the extrusion force is 0.35 MPa.
[0152] In the related art, battery cells may be subjected to external squeezing during use, and the electrolyte in the electrode assembly may be separated from the electrode assembly under the action of squeezing, forming free electrolyte. The free electrolyte in the battery cell may leak, causing corrosion to the battery cell, leading to risks such as battery cell failure. However, the embodiment of the present application can effectively squeeze out the liquid electrolyte inside the battery cell by performing an squeezing test on the battery cell, thereby more accurately judging whether there is flowing liquid electrolyte between the battery cell shell and the electrode assembly, and determining the content of free electrolyte. When the battery cell of the embodiment of the present application meets the above conditions, after squeezing, the content of free electrolyte in the battery cell is extremely small, or even the battery cell basically contains no free electrolyte, which can significantly improve the reliability and cycle performance of the battery cell.
[0153] For example, M2 can be 0 mL, 0.05 mL, 0.1 mL, 0.15 mL, 0.2 mL, 0.25 mL, 0.3 mL, 0.35 mL, 0.4 mL, 0.45 mL, 0.5 mL, or a range consisting of any two of the foregoing values. An M2 of 0 mL indicates zero free electrolyte, meaning that substantially no free electrolyte remains within the battery cell after the extrusion test.
[0154] In some embodiments, a voltage of 200 V is provided to the battery cell to form a loop for 4 hours, and the absolute value of the temperature change of the battery cell is ≤ 4°C.
[0155] For example, when the negative terminal and outer casing of a battery cell are connected to a 200V voltage to form a current loop, the battery cell's temperature fluctuates within 4°C over a 4-hour period, without any failures such as fire or explosion. In particular, when the free electrolyte y = 0, the temperature fluctuation range is minimal, significantly improving the reliability of the battery cell.
[0156] In some embodiments, the mass per unit volume of the liquid-absorbing polymer in the electrode plate is A1, the mass per unit volume of the liquid-absorbing polymer in the isolation membrane is A2, 1.0≤A1 / A2≤1.6; optionally, 1.2≤A1 / A2≤1.5.
[0157] When the battery cell meets the above conditions, the electrode plate has good liquid absorption performance and the isolation membrane has good liquid retention performance. The two work together. During the battery cell's cyclic charge and discharge process, the electrolyte is not easily squeezed out of the electrode assembly, and can have a good infiltration effect on the electrode plate, thereby improving the cycle performance of the battery cell.
[0158] Illustratively, A1 / A2 may be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, or a range consisting of any two of the above values.
[0159] In some embodiments, the electrode plate further comprises a liquid-retaining polymer. The introduction of the liquid-retaining polymer can improve the liquid-retaining capacity of the electrode plate, thereby improving the wettability of the electrolyte to the electrode plate.
[0160] In some embodiments, the unit volume mass of the liquid-retaining polymer in the electrode plate is B1, the unit volume mass of the liquid-retaining polymer in the isolation membrane is B2, 0.4≤B1 / B2≤0.9; optionally, 0.5≤B1 / B2≤0.8.
[0161] When the battery cell meets the above conditions, the electrode plate has good liquid absorption performance and the isolation membrane has good liquid retention performance. The two work together. During the battery cell's cyclic charge and discharge process, the electrolyte is not easily squeezed out of the electrode assembly, and can have a good infiltration effect on the electrode plate, thereby improving the cycle performance of the battery cell.
[0162] Illustratively, B1 / B2 may be 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or a range consisting of any two of the above values.
[0163] In some embodiments, the liquid-absorbing polymer includes at least one of an ether polymer and an ester polymer.
[0164] [Ether polymers]
[0165] In some embodiments, the liquid-absorbing polymer includes an ether polymer, and the ether polymer is made into a sheet structure; the sheet structure is formed at (T m2 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K1, 1<K1<∞, T m2 °C represents the melting temperature of the ether polymer.
[0166] Specifically, the sheet structure is prepared as follows: the ether polymer is vacuum dried at 80°C for 12 hours. The dried ether polymer is hot-pressed into a sheet by a flat vulcanizer, and the hot-pressing temperature is set to (T m2 The sample is then removed from the press after 2 minutes of calendering and placed on another vulcanizing press of the same model for cold pressing at a pressure of 10 MPa. A polymer disc (sheet structure) of fixed size is obtained using a circular mold with a diameter of 25 mm. For example, the sheet structure can be a disc with a thickness of 1-2 mm and a diameter of 25 mm; alternatively, a sample can be prepared according to the sample standard required by the test equipment.
[0167] According to the conclusions of classical linear viscoelasticity, for polymers, especially linear polymers, the elastic modulus G'-dissipation modulus G" in the terminal region of the elastic modulus G'-dissipation modulus G" curve (the interval approaching the maximum angular velocity) conforms to frequency dependence, and the longest chain of the polymer plays a role in the viscoelastic behavior.
[0168] The specific steps of the dynamic frequency sweep test are as follows: The dynamic frequency sweep test was performed using a TA-AR2000EX rotational rheometer (TAinstruments, USA) with a parallel plate diameter of 25 mm and a thickness of 0.9 mm. To ensure that the test was in the linear point-bounce region, the strain during the dynamic frequency sweep test was 2% and the test temperature was T m2 +20℃, test frequency sweep range: 500rad / s≤w 2 ≤0.05rad / s, so as to obtain data in the lowest possible frequency range.
[0169] The dynamic frequency sweep test can characterize the degree of entanglement of molecular chains under solid-phase melting (melt state). Compared with linear structures or short-chain branched structures, long-branched structures, network structures, and low-crosslinked structures have a high degree of entanglement, which will show deviation from linear terminal behavior. Ether polymers exhibit solid-phase behavior. When the ether polymers of the present application meet the above range, the entanglement state of the molecular chains can be further reduced, which is conducive to the diffusion of solvent molecules in the electrolyte between the molecular chains; moreover, the ether polymers still maintain a certain degree of molecular chain entanglement and can form a gel-like substance with the electrolyte, thereby improving the cycle performance and storage performance of the battery cell.
[0170] In some embodiments, 1<K1≤100; alternatively, 1<K1≤10. For example, K1 can be 1.01, 1.1, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000, or a range consisting of any two of the above values.
[0171] In some embodiments, the glass transition temperature of the ether polymer is T g2 , its unit is ℃, -100≤T g2 ≤50; optionally, -80≤T g2 ≤30. For example, the glass transition temperature of the ether polymer may be -100°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range consisting of any two of the above values.
[0172] In some embodiments, the ether polymer includes a structural unit represented by formula (BI),
[0173] In formula (BI), R 21 and R 22 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; R 23 This includes substituted or unsubstituted C1-C5 methylene groups.
[0174] In some embodiments, R 21 and R 22 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C2 alkyl group.
[0175] In some embodiments, R 23 It includes single bonds, substituted or unsubstituted C1-C4 methylene groups.
[0176] Illustratively, the ether polymer includes at least one of the structural units represented by formula (BI-1) to the structural units represented by formula (BI-8),
[0177] In some embodiments, the ether polymer comprises a structural unit represented by formula (BII),
[0178] In formula (BII), R 24 to R 27 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 alkoxy group or an ether group, and R 24 to R 27At least one of them contains a substituted or unsubstituted C1-C3 alkoxy group or an ether group.
[0179] In some embodiments, R 24 to R 27 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C2 alkyl group, a substituted or unsubstituted C1-C2 alkoxy group or an ether group, and R 24 to R 27 At least one of them contains a substituted or unsubstituted C1-C2 alkoxy group or an ether group.
[0180] In some embodiments, the ether polymer includes at least one of the structural units represented by formula (BII-1) to the structural units represented by formula (BII-7),
[0181] The monomers used in the above-mentioned ether polymers are polycyclic rings, such as structures with six or less members, or short-chain monomers, which are conducive to the polymerization to form a high-content -O- structure. This type of structure has a low degree of entanglement, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte and easily form a gel-like substance with the electrolyte, thereby improving the cycle performance and storage performance of the battery monomer.
[0182] The above-mentioned polymers are only examples of the structural groups of the main molecular chain. In the embodiments of the present application, the polymers can also be obtained by copolymerizing the above-mentioned structural groups with other types of structural groups (such as olefin structural units, ester monomers, nitrile monomers, amide monomers and other structural units).
[0183] When the above-mentioned groups are substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom. These substituents are high-pressure-resistant substituents, which are more conducive to stabilizing the structure of the polymer. Halogen atoms may include fluorine atoms, chlorine atoms, bromine atoms, and the like.
[0184] In some embodiments, the degree of polymerization n of the ether polymer is a positive integer selected from 1,500 to 25,000.
[0185] Optionally, the polymerization degree n of the ether polymer is a positive integer selected from 3,000 to 18,000.
[0186] In some embodiments, the molecular weight of the polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.
[0187] For example, the molecular weight of the polymer may be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×105 g / mol, 8×10 5 g / mol, 1×10 6 g / mol or a range consisting of any two of the above values.
[0188] [Ester polymer]
[0189] In some embodiments, the liquid-absorbing polymer comprises an ester polymer, wherein the ester polymer is made into a sheet structure; the sheet structure is (T m3 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K2, 1<K2<∞, T m3 °C represents the melting temperature of the ester polymer.
[0190] When the ester polymer of the embodiment of the present application meets the above range, the entanglement state of the molecular chains can be further reduced, which is beneficial to the diffusion of solvent molecules in the electrolyte between the molecular chains; and the ether polymer still maintains a certain molecular chain entanglement state, can form a gel-like substance with the electrolyte, can increase the liquid absorption rate, and thereby improve the cycle performance and storage performance of the battery cell.
[0191] In some embodiments, 1<K2≤100; optionally, 1<K2≤10.
[0192] Illustratively, K2 may be 1.01, 1.1, 1.2, 1.5, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000, or a range consisting of any two of the above values.
[0193] In some embodiments, the glass transition temperature of the ester polymer is T g3 , its unit is ℃, -100≤T g3 ≤50; optionally, -80≤T g3 ≤30.
[0194] For example, the glass transition temperature of the ester polymer may be -100°C, -90°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range consisting of any two of the above values.
[0195] In some embodiments, the ester polymer comprises a structural unit represented by formula (CI),
[0196] In formula (CI), R 31 、R 32 and R 33Each independently includes a hydrogen atom, or a substituted or unsubstituted C1-C8 alkyl group; R 34 Including substituted or unsubstituted C1-C8 alkyl, or substituted or unsubstituted C1-C8 hydroxyalkyl; optionally, R 34 It includes substituted or unsubstituted C1-C6 alkyl groups, or substituted or unsubstituted C1-C6 hydroxyalkyl groups.
[0197] Optionally, R 31 This includes a hydrogen atom, or a substituted or unsubstituted methyl group.
[0198] Optionally, R 32 and R 33 Each independently includes a hydrogen atom.
[0199] Optionally, R 34 It includes substituted or unsubstituted C1-C4 alkyl groups, or substituted or unsubstituted C1-C4 hydroxyalkyl groups.
[0200] Illustratively, the ester polymer includes at least one of the structural units represented by formula (CI-1) to the structural units represented by formula (CI-15),
[0201] In some embodiments, the ester polymer comprises a structural unit represented by formula (CII),
[0202] In formula (CII), R 35 This includes substituted or unsubstituted C2-C6 methylene groups.
[0203] Optionally, R 35 Each independently includes a substituted or unsubstituted C2-C4 methylene group.
[0204] Illustratively, the ester polymer includes at least one of the structural units represented by formula (CII-1) to the structural units represented by formula (CII-5),
[0205] The molecular chains of the above-mentioned ester polymers have a low degree of entanglement, which is conducive to improving the flexibility of the molecular chains. The molecular chains can fully stretch in the electrolyte and easily form a gel-like substance with the electrolyte.
[0206] The above-mentioned polymers are only examples of the structural groups of the main molecular chain. In the embodiments of the present application, the polymers can also be obtained by copolymerizing the above-mentioned structural groups with other types of structural groups (such as olefin structural units, ester monomers, nitrile monomers, amide monomers and other structural units).
[0207] When the above-mentioned groups are substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom (e.g., a chlorine atom, a fluorine atom, or a bromine atom). The above-mentioned substituents are high-pressure-resistant substituents, which are more conducive to stabilizing the structure of the polymer. The above-mentioned substituents are high-pressure-resistant substituents, which are more conducive to stabilizing the structure of the polymer.
[0208] In some embodiments, the degree of polymerization n of the ester polymer is a positive integer selected from 800 to 20,000.
[0209] Optionally, the polymerization degree n of the ester polymer is a positive integer selected from 1,000 to 15,000.
[0210] In some embodiments, the molecular weight of the ester polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.
[0211] For example, the molecular weight of the ester polymer may be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.5×10 6 g / mol or a range consisting of any two of the above values.
[0212] In some embodiments, the liquid-retaining polymer includes at least one of a fluorinated polymer and an aldehyde-ketone polymer.
[0213] In some embodiments, the liquid-retaining polymer comprises a fluorinated polymer having a crystallinity of X 0. C1 ,0<X C1 ≤30%; the melting temperature of the fluoropolymer is T m1 , its unit is ℃, 0<T m1 ≤140.
[0214] Crystallization refers to the process in which atoms, ions or molecules in a material are arranged in a certain spatial order to form an orderly structure. The conformation of the polymer in the crystallization is determined by both intramolecular and intermolecular factors. The intermolecular force will affect the packing density between molecular chains. C1 It is used to characterize the degree of crystallinity in the material, which can be measured by differential scanning calorimetry (DSC). Specifically, the test steps are as follows: take 0.5g to 0.8g of sample, place the sample in a carrier crucible, and perform temperature rise and fall treatment on the sample under a nitrogen atmosphere, with a heating rate of 10℃ / min from the intrinsic T g1The initial temperature is 20℃ lower and then heated to the intrinsic T m1 The cut-off temperature of the process is 20℃ higher. The actual glass transition temperature T of the material is determined according to the endothermic and exothermic peak or transition point of the material in the process. g1 and melting temperature T m1 wait.
[0215] As a result, fluoropolymers have relatively low crystallinity and melting temperature, which makes the molecular chains tend to be loose, the interaction force between the molecular chains is small, adjacent molecular chains are easily opened, and the chain segment movement is achieved through intermolecular rotation, forming a molecular chain structure with high flexibility; and the fluoropolymers and the electrolyte in the battery cell can form a gel-like substance, thereby improving the cycle performance of the battery cell.
[0216] For example, the crystallinity X of the fluorinated polymer measured by differential scanning calorimetry is C1 It can be 5%, 10%, 15%, 20%, 25%, 30% or a range consisting of any two of the above values.
[0217] For example, the melting temperature of the fluorinated polymer may be 10° C., 20° C., 50° C., 70° C., 90° C., 100° C., 120° C., 140° C., or a range consisting of any two of the foregoing values.
[0218] In some embodiments, the glass transition temperature of the fluorinated polymer is T g1 , its unit is ℃, -150≤T g1 ≤60.
[0219] The glass transition temperature is the temperature at which the chain segments of a polymer transition from freezing to movement. The glass transition temperature has a certain influence on the flexibility of the polymer molecular chain. The lower the glass transition temperature, the better the flexibility of the polymer molecular chain at room temperature. The higher the glass transition temperature, the worse the flexibility of the molecular chain at room temperature. The glass transition temperature can be measured by differential scanning calorimetry (DSC). The lower the glass transition temperature of a polymer, the better the segment flexibility of the molecular chain, and the easier it is for adjacent molecular chains to be opened. For example, the glass transition temperature of a fluorinated polymer can be -150°C, -120°C, -100°C, -80°C, -60°C, -30°C, 0°C, 30°C, 60°C, or a range consisting of any two of the above values.
[0220] In some embodiments, the fluorinated polymer comprises a structural unit represented by formula (AI),
[0221] In formula (AI), R 11 、R 12 、R 13 and R 14Each independently includes a hydrogen atom, a fluorine atom, a bromine atom, a substituted or unsubstituted C1-C3 alkyl group or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 、R 12 、R 13 and R 14 At least one of them contains a fluorine atom.
[0222] In some embodiments, the fluorinated polymer comprises a structural unit represented by formula (AII),
[0223] In formula (AI) and formula (AII), R 11 、R 12 、R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a bromine atom, a substituted or unsubstituted C1-C3 alkyl group or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 、R 12 、R 13 and R 14 At least one of them contains a fluorine atom.
[0224] In some embodiments, the fluorinated polymer comprises a structural unit represented by formula (AII),
[0225] In formula (AIII), R 15 This includes single bonds, substituted or unsubstituted C1-C3 alkyl groups.
[0226] When the above-mentioned groups are substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom. The above-mentioned substituents are high-pressure resistant substituents, which are more conducive to stabilizing the structure of the polymer. The halogen atom may include a fluorine atom, a chlorine atom, a bromine atom, etc. Alternatively, the halogen atom includes a fluorine atom.
[0227] In the embodiments of the present application, the polymer may also be obtained by copolymerizing the above structural groups with a small amount of other types of structural groups (such as olefin structural units, ester monomers, nitrile monomers, amide monomers, etc.).
[0228] In some embodiments, p is a positive integer selected from 1 to 3.
[0229] In some embodiments, the degree of polymerization n of the fluorinated polymer is selected from a positive integer ranging from 1,000 to 30,000.
[0230] In some embodiments, R 11 、R 12 、R 13 and R 14Each independently includes a hydrogen atom, a fluorine atom, a bromine atom, a substituted or unsubstituted C1-C2 alkyl group or a substituted or unsubstituted C1-C2 alkoxy group; further optionally, R 11 、R 12 、R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, a fluoromethyl group, a methoxy group or a perfluoromethoxy group.
[0231] In some embodiments, the fluorinated polymer includes at least one of the structural units represented by formula (AI-1) to the structural units represented by formula (AI-11),
[0232] In some embodiments, the fluorinated polymer includes at least one of the structural units represented by formula (AII-1) to the structural units represented by formula (AII-5),
[0233] In some embodiments, the fluorinated polymer includes at least one of the structural units represented by formula (AIII-1) to the structural units represented by formula (AIII-3),
[0234] Illustratively, the fluorinated polymer includes one or more of polyperfluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroethylene propylene copolymer (FEP), perfluoroalkoxy polymer (PFA), perfluoropolyether (PFPE), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE) and perfluoro (1-butenyl vinyl ether) polymer (CYTOP for short).
[0235] Optionally, the fluorinated polymer includes one or more of polyperfluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroethylene propylene copolymer (FEP), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), and polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE).
[0236] The fluoropolymer may be derived from one or more of the following monomers: fluorocycloethane, vinyl fluoride, 1,2-difluoroethylene, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene, 3,3,3-trifluoropropylene, trifluoropropylene, tetrafluoropropylene, and pentafluoropropylene. Alternatively, the fluoropolymer may be derived from at least two of the following monomers: fluorocycloethane, vinyl fluoride, 1,2-difluoroethylene, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene, 3,3,3-trifluoropropylene, trifluoropropylene, tetrafluoropropylene, and pentafluoropropylene.
[0237] The monomers used in the above-mentioned fluorinated polymers are all short-chain monomers, which are conducive to polymerization to form straight-chain linear structures or short-chain branched structures. This type of structure has a low degree of entanglement, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte, thereby facilitating the formation of a three-dimensional gel-like substance between the polymer and the electrolyte, which is conducive to further improving the liquid absorption rate.
[0238] In some embodiments, the degree of polymerization n of the fluorinated polymer is selected from a positive integer ranging from 5,000 to 20,000.
[0239] In some embodiments, the molecular weight of the fluorinated polymer is 1.2×10 5 g / mol to 1.5×10 6 g / mol; optional: 1.2×10 5 g / mol to 1.0×10 6 When the molecular weight of the polymer is within the above range, the polymer can have excellent liquid-retaining ability, thereby improving the liquid-retaining ability of the separator.
[0240] For example, the molecular weight of the polymer may be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.5×10 6 g / mol or a range consisting of any two of the above values.
[0241] [Ketone-aldehyde polymers]
[0242] In some embodiments, the liquid-retaining polymer comprises an aldehyde-ketone polymer, wherein the aldehyde-ketone polymer is made into a sheet structure; the sheet structure is (T m4 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K3, 0.8≤K3<∞, T m4°C represents the melting temperature of the aldehyde-ketone polymer.
[0243] In some embodiments, 0.8≤K3≤100; optionally, 0.8≤K3≤10.
[0244] Illustratively, K3 may be 0.8, 0.9, 1, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000, or a range consisting of any two of the above values.
[0245] In some embodiments, the glass transition temperature of the aldehyde-ketone polymer is T g4 , its unit is ℃, -100≤T g4 ≤50; optionally, -80≤T g4 ≤30.
[0246] For example, the glass transition temperature of the aldehyde-ketone polymer may be -100°C, -90°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range consisting of any two of the above values.
[0247] In some embodiments, the aldehyde-ketone polymer comprises a structural unit represented by formula (DI),
[0248] In formula (DI), R 41 Including single bonds, substituted or unsubstituted C1-C6 methylene; R 42 including hydrogen atoms, substituted or unsubstituted C1-C6 alkyl groups;
[0249] Optionally, R 41 including single bonds, substituted or unsubstituted C1-C2 methylene groups;
[0250] Optionally, R 42 This includes hydrogen atoms, and substituted or unsubstituted C1-C3 alkyl groups.
[0251] In the embodiments of the present application, a single bond indicates that the group does not exist, and the atoms on both sides of the group are connected by a single bond, for example, R 41 is a single bond, indicating R 41 The carbon atoms on both sides are connected by single bonds.
[0252] Illustratively, the aldehyde-ketone polymer includes at least one of the structural units represented by formula (DI-1) to the structural units represented by formula (DI-6),
[0253] Illustratively, the aldehyde-ketone polymer includes a structural unit represented by formula (DII),
[0254] In formula (DII), R 43 to R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from an integer from 0 to 5, and at least one of r and s is selected from a positive integer; optionally, R 43 to R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C2 hydroxyalkyl group, or a substituted or unsubstituted C1-C2 alkoxy group.
[0255] In some embodiments, the aldehyde-ketone polymer includes at least one of the structural units represented by formula (DII-1) to the structural units represented by formula (DII-4),
[0256] The molecular chain entanglement degree of the above-mentioned aldehyde-ketone polymer is low, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte, which is conducive to forming a gel-state substance with the electrolyte.
[0257] The above polymers are only examples of the structural groups of the main molecular chain. In the embodiments of the present application, the polymers can also be obtained by copolymerizing the above structural groups with other types of structural groups (such as olefin structural units, enol structural units, acrylonitrile structural units, etc.).
[0258] When the above-mentioned groups are substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonyl group, a carboxyl group, an ester group, a chlorine atom, a fluorine atom, and a bromine atom. These substituents are high-pressure-resistant substituents and are more conducive to stabilizing the structure of the polymer.
[0259] In some embodiments, the degree of polymerization n of the aldehyde-ketone polymer is a positive integer selected from 500 to 15,000.
[0260] Optionally, the degree of polymerization n of the aldehyde-ketone polymer is selected from a positive integer ranging from 500 to 10,000.
[0261] In some embodiments, the molecular weight of the aldehyde-ketone polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.
[0262] For example, the molecular weight of the aldehyde-ketone polymer may be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6g / mol, 1.0×10 6 g / mol or a range consisting of any two of the above values.
[0263] In some embodiments, a liquid-retaining polymer is added to a first solvent at 70°C to form a polymer system; after the polymer system is allowed to stand at 70°C for 8 hours and at 25°C for ≥24 hours, the polymer system is filtered through a 200-mesh filter to leave a first substance, wherein the mass of the liquid-retaining polymer is q, and its unit is g; the mass of the first substance is m, and its unit is g; the liquid-retaining polymer and the first substance satisfy: 5≤m / q≤1000.
[0264] The liquid-retaining polymer has excellent liquid absorption and liquid-retaining properties, which is beneficial to improving the liquid-retaining capacity of the isolation membrane.
[0265] In some embodiments, 10≤m / q≤1000; further optionally, 10≤m / q≤50. For example, m / q can be 5, 10, 20, 25, 28, 30, 32, 35, 40, 50, 80, 100, 200, 500, 1000, or a range consisting of any two of the above values.
[0266] The polymer system is allowed to stand at 70°C for 8 hours and at 25°C for ≥24 hours. After undergoing two stages of standing treatment, part of the polymer system is transformed into a gel-state substance through swelling and adsorption; the polymer system is in contact with the electrolyte, the polymer molecular chains stretch and open, and the electrolyte can diffuse between the molecular chains. The polymer molecular chains swell and adsorb the electrolyte, which is beneficial to improving the liquid absorption capacity and can further enhance the cycle performance of the battery cell.
[0267] Illustratively, based on the mass of the polymer system, the ratio of the mass content of the liquid-absorbing polymer to the mass content of the first solvent ranges from 1:100 to 1:10, such as 3:50.
[0268] Exemplarily, the first solvent is the same as or similar to the solvent of the electrolyte, and the first solvent may include at least one of a carbonate solvent and an ether solvent. For example, the carbonate solvent includes a cyclic carbonate solvent and / or a linear carbonate solvent.
[0269] As examples of the cyclic carbonate solvent, the cyclic carbonate solvent includes one or more of ethylene carbonate EC, vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinyl ethylene carbonate VEC, and dioctyl carbonate CC.
[0270] As examples of the linear carbonate solvent, the linear carbonate solvent includes one or more of dimethyl carbonate DMC, diethyl carbonate DEC, ethyl methyl carbonate EMC, diphenyl carbonate DPC, methyl allyl carbonate MAC, and polycarbonate VA.
[0271] As examples of the ether solvent, the ether solvent includes one or more of tetrahydrofuran THF, 2-methyltetrahydrofuran 2me-thf, 1,3-dioxolane DOL, dimethoxymethane DMM, 1,2-dimethoxyethane DME, and diglyme DG.
[0272] Optionally, the first solvent may also contain a lithium salt and an electrolyte additive, such as lithium hexafluorophosphate, vinylene carbonate VC, fluorovinylene carbonate FEC, and the like.
[0273] In this application, m / q is also referred to as the precipitation value, which characterizes the ability of the liquid-absorbing polymer and solvent to transform into a gel-state substance.
[0274] The first substance mainly includes a gel-state substance formed by a liquid-retaining polymer and a first solvent. In this type of gel-state substance, the molecular structure of the polymer basically does not change.
[0275] In some embodiments, the first substance is dried at 80° C. for 12 hours to remove the first solvent in the first substance. Detection by infrared spectrophotometry (IR) or nuclear magnetic resonance (NMR) testing shows that the main component of the first substance after drying is the liquid-absorbing polymer described above.
[0276] By increasing the temperature, embodiments of the present application can achieve stretching of the liquid-retaining polymer molecular chains within the safe operating temperature range of the battery cell, promoting mutual attraction and physical bonding between the polymer molecular chains and the electrolyte. At room temperature, the activity of the liquid-retaining and liquid-absorbing polymer molecular segments decreases, allowing them to remain attached to the separator and lock the electrolyte within the space surrounding the liquid-retaining polymer, forming a gel or gel-like state. This can increase the transmission rate of active ions, such as lithium ions, and improve cycling performance.
[0277] The relevant parameters of the polymer according to the embodiment of the present application can be detected by the following methods:
[0278] The groups of the polymers of the embodiments of the present application can be detected by infrared spectrophotometry IR. Specifically, the liquid-retaining polymer is tested using a Thermo Nicolet Nexus 670 attenuated total reflectance Fourier transform infrared spectrometer (FTIR-ATR), and then tested in accordance with the standard GB / T6040-2002. The test range is: ATR method 600-4000 cm -1 ; Repeatability: ±2cm -1 ; Resolution: better than 4cm -1; Transmission depth 0.2~0.6μm.
[0279] The structure of the polymer according to the embodiment of the present application can be tested by nuclear magnetic resonance (NMR). Specifically, 1H NMR and 13C NMR are performed on a Varian Mercury Plus-400 NMR spectrometer at a test temperature of 20° C., TMS as an internal standard, CDCl 3 as a solvent, and a proton resonance frequency of 400 MHz.
[0280] The polymer monomer type of the polymer according to the embodiment of the present application (especially suitable for monomers that account for a relatively small proportion in the polymer) can be tested by pyrolysis-gas chromatography-mass spectrometry. The specific testing steps are as follows: accurately weigh 0.5 mg of sample and put it into the sample cup. After fixing it to the injection rod, it is loaded into the pyrolyzer installed near the GC (gas chromatography) injection port. After the pyrolyzer temperature reaches the set temperature, press the injection button, and the sample cup falls rapidly into the core of the pyrolysis furnace by free fall. In the inert gas N2 atmosphere, the volatile components are instantly vaporized and carried into the gas chromatography column by the carrier gas for separation. Finally, it is detected by a flame ionization detector FID or a mass spectrometer MS to obtain a gas chromatogram or a total ion current diagram.
[0281] The molecular weight of the polymer in the embodiment of the present application has a well-known meaning in the art and can be measured using commonly used equipment and methods in the art. Gel permeation chromatography (GPC) testing can be used. The specific testing steps are as follows: take an appropriate amount of the sample to be tested (the sample concentration is sufficient to ensure 8%-12% shading), add 20 ml of deionized water, and simultaneously supercharge for 5 minutes (53 KHz / 120 W) to ensure that the sample is completely dispersed, and then measure the sample in accordance with GB / T19077-2016 / ISO 13320:2009 standard.
[0282] Alternatively, a multi-angle laser light scattering (MALLS) instrument was used for testing. Specifically, a GPC coupled with a Dawn Heleos II multi-angle laser light scattering device, an Optilab T-rEX refractive index (RI) detector, and a Visco Star II viscometer (Wyatt Technology Corporation, USA) was used. Testing was conducted at 30°C, using tetrahydrofuran as the mobile phase at a flow rate of 1.0 ml / min. SEC-SAMLL data were processed using the commercial ASTRA6 software to obtain molecular weight parameters.
[0283] In some embodiments, the separator includes a porous substrate, and the liquid-retaining polymer is distributed in the pores of the porous substrate.
[0284] In other embodiments, the separator includes a porous substrate and a polymer layer disposed on at least one surface of the porous substrate, wherein the polymer layer includes a liquid-retaining polymer. The polymer layer disposed on at least one surface of the porous substrate means that the polymer layer can be disposed on one surface of the porous substrate or on both surfaces of the porous substrate. The liquid-retaining polymer can be dispersed in a solvent to form a polymer mixture system, and the polymer mixture system can be applied to the porous substrate via a coating process such as atomized spray coating or gravure coating.
[0285] The embodiments of the present application do not particularly limit the material of the porous substrate. Any known porous substrate with good chemical and mechanical stability can be selected. For example, the porous substrate may include at least one of a porous polyolefin-based resin film (e.g., at least one of polyethylene, polypropylene, and polyvinylidene fluoride), a porous glass fiber, and a porous non-woven fabric. The porous substrate may be a single-layer film or a multi-layer composite film. When the porous substrate is a multi-layer composite film, the materials of each layer may be the same or different.
[0286] In some embodiments, the porous substrate has a porosity greater than or equal to 25%, and can optionally be between 25% and 50%. When the porosity of the porous substrate is within this range, the air permeability of the porous substrate can be increased, which is beneficial for the migration of active ions. Furthermore, due to the relatively low porosity, the mechanical properties of the porous substrate can be improved, and the porous substrate can provide good support for the polymer layer.
[0287] In some embodiments, the thickness of the porous substrate may be less than or equal to 16 μm, and may be 5 μm to 12 μm. For example, the thickness of the porous substrate may be 1 μm, 2 μm, 3 μm, 5 μm, 10 μm, 12 μm, 15 μm, 16 μm, or a range consisting of any two of the aforementioned values.
[0288] Optionally, the polymer layer includes heat-resistant particles. The heat-resistant particles and the liquid-retaining polymer act synergistically to further enhance the overall heat resistance and ion transport properties of the separator. The liquid-retaining polymer and heat-resistant particles can be dispersed in a solvent to form a polymer mixture system, which is then applied to the porous substrate via a coating process such as atomized spray coating or gravure coating.
[0289] In some embodiments, based on the total mass of the polymer layer, the ratio of the mass percentage of the liquid-retaining polymer to the mass percentage of the heat-resistant particles is (0.2 to 5.0):1, or optionally (0.5 to 2.0):1. When the contents of the heat-resistant particles and the liquid-retaining polymer are within the above ranges, the overall heat resistance and ion transport properties of the separator can be further improved. Illustratively, the ratio of the mass percentage of the liquid-retaining polymer to the mass percentage of the heat-resistant particles can be 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.8:1, 1.0:1, 1.2:1, 1.5:1, 1.8:1, 2.0:1, 2.5:1, 2.8:1, 3.0:1, 3.2:1, 3.5:1, 3.8:1, 4.0:1, 4.2:1, 4.5:1, 4.8:1, 5.0:1 or a range consisting of any two of the above values.
[0290] In some embodiments, the thickness of the polymer layer may be 0.5 μm to 3.0 μm; optionally, 1.0 μm to 2.0 μm. When the thickness of the polymer layer is within the above range, the heat resistance and ion transmission performance of the isolation membrane as a whole can be further improved. For example, the thickness of the polymer layer may be 0.5 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.3 μm, 2.5 μm, 2.8 μm, 3.0 μm, or a range consisting of any two of the above values.
[0291] Optionally, the separator may further include a heat-resistant coating, wherein the heat-resistant coating is located on at least one surface of the porous substrate, and the polymer layer is located on a side of the heat-resistant coating facing away from the porous substrate.
[0292] The heat-resistant coating may include heat-resistant particles. In some embodiments, the heat-resistant particles include at least one of inorganic particles and organic particles. By adding heat-resistant particles, the heat resistance of the isolation film can be improved.
[0293] In some embodiments, the mass percentage of the inorganic particles in the heat-resistant coating is ≤ 30. For example, the mass percentage of the inorganic particles in the heat-resistant coating is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, or a range consisting of any two of the above values.
[0294] The inorganic particles may include at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having the ability to transport active ions, and inorganic particles capable of electrochemical oxidation and reduction.
[0295] In some embodiments, inorganic particles having a dielectric constant of 5 or higher may include boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), silicon oxide SiO x (0<x≤2), tin dioxide (SnO2), titanium oxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), hafnium dioxide (HfO2), cerium oxide (CeO2), zirconium titanate (ZrTiO3), barium titanate (BaTiO3), magnesium fluoride (MgF2), Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti n O3 (abbreviated as PLZT, 0<m<1, 0<n<1) and Pb(Mg3Nb 2 / 3 ) at least one of O3-PbTiO3 (abbreviated as PMN-PT).
[0296] In some embodiments, the inorganic particles capable of transporting active ions may include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0<x<2, 0<y<3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0<x<2, 0<y<1, 0<z<3), (LiAlTiP) x O y Glass-like (0<x<4, 0<y<13), lithium lanthanum titanate (Li x La y TiO3, 0<x<2, 0<y<3), lithium germanium thiophosphate (Li x Ge y P z S w , 0<x<4, 0<y<1, 0<z<1, 0<w<5), lithium nitride (Li x N y , 0<x<4, 0<y<2), SiS2 type glass (Li x Si y S z , 0<x<3, 0<y<2, 0<z<4) and P2S5 type glass (Li x P y S z , 0<x<3, 0<y<3, 0<z<7).
[0297] In some embodiments, the inorganic particles capable of electrochemical oxidation and reduction may include at least one of lithium-containing transition metal oxides, lithium-containing phosphates with olivine structures, carbon-based materials, silicon-based materials, tin-based materials, and lithium titanium compounds.
[0298] In some embodiments, the heat-resistant coating may also include other organic particles, for example, the organic particles may include polystyrene, polyethylene, polyimide, melamine resin, phenolic resin, polypropylene, polyester (such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate), polyphenylene sulfide, polyaramid, polyamideimide, polyimide, copolymer of butyl acrylate and ethyl methacrylate and mixtures thereof.
[0299] In some embodiments, the heat-resistant coating may further include a binder. For example, the binder may include at least one of an aqueous solution-based acrylic resin (e.g., a homopolymer of acrylic acid, methacrylic acid, or sodium acrylate monomers, or a copolymer with other comonomers), polyvinyl alcohol (PVA), an isobutylene-maleic anhydride copolymer, and polyacrylamide.
[0300] In some embodiments, the thickness of the heat-resistant coating is ≤ 4 μm. This helps to increase the energy density of the battery cell. In the embodiments of the present application, the thickness of the heat-resistant coating refers to the thickness of the heat-resistant coating located on a single side of the substrate. For example, the thickness of the heat-resistant coating can be 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, or a range consisting of any two of the above values.
[0301] In some embodiments, the coating weight of the liquid retaining polymer is 0.5 mg / 1540.25 mm 2 Up to 5mg / 1540.25mm 2 .
[0302] When the coating weight is within the above range, the liquid retention capacity of the separator can be further improved.
[0303] Optionally, the coating weight of the polymer layer can be 0.5 mg / 1540.25 mm 2 Up to 3.5mg / 1540.25mm 2 .
[0304] For example, the coating weight of the polymer layer can be 0.5 mg / 1540.25 mm 2 、0.6mg / 1540.25mm 2 、0.8mg / 1540.25mm 2 、1.0mg / 1540.25mm 2、1.2mg / 1540.25mm 2 、1.5mg / 1540.25mm 2 、1.8mg / 1540.25mm 2 , 2.0mg / 1540.25mm 2 , 2.5mg / 1540.25mm 2 、3mg / 1540.25mm 2 、3.5mg / 1540.25mm 2 、4mg / 1540.25mm 2 4.5mg / 1540.25mm 2 、5mg / 1540.25mm 2 Or a range consisting of any two of the above values.
[0305] In the embodiment of the present application, the coating weight refers to the coating weight of the liquid-retaining polymer on one side of the isolation film, which can be detected by using equipment and methods known in the art, for example, by cutting the same mother roll substrate and isolation film into 1540.25mm 2 The weight of 10 isolation film discs is respectively weighed, and the coating weight of the highly liquid-absorbent polymer in the isolation film can be obtained by calculation.
[0306] [Positive electrode]
[0307] The battery cell includes a positive electrode plate, and the positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on the positive electrode current collector.
[0308] In some embodiments, the positive electrode film layer includes a positive electrode active material and a liquid-absorbing polymer.
[0309] As some examples, the positive electrode film layer includes a polymer layer containing a liquid-absorbing polymer and a positive electrode active material layer containing positive electrode active material particles. The positive electrode active material layer is arranged on at least one surface of the positive electrode collector, and the polymer layer is arranged on the surface of the positive electrode active material layer away from the positive electrode collector.
[0310] As some other examples, there are a plurality of positive electrode active material particles, a gap exists between two adjacent positive electrode active material particles, and the liquid-absorbing polymer is distributed in the gap.
[0311] In some embodiments, the positive electrode film layer may further include a liquid-retaining polymer.
[0312] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on either or both of the two facing surfaces of the positive electrode current collector.
[0313] In some embodiments, 1.20≤v / λ≤4.50. For example, v / λ can be 1.20, 1.40, 1.80, 2.00, 2.50, 3.00, 3.50, 3.60, 3.80, 3.90, 4.0, 4.2, 4.5, or a range consisting of any two of the above values.
[0314] In some embodiments, the mass percentage of the liquid-absorbing polymer is 0.1% to 1.5% based on the mass of the positive electrode active material layer.
[0315] When the mass percentage of the liquid-absorbing polymer is within the above range, the liquid-absorbing capacity of the positive electrode active material layer can be significantly improved. For example, the mass percentage of the liquid-absorbing polymer can be 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, or a range consisting of any two of the above values.
[0316] The positive electrode active material layer includes a positive electrode active material, which can be a positive electrode active material commonly known in the art for use in battery cells. For example, the positive electrode active material can include at least one of the following materials: a lithium-containing phosphate compound, a lithium-containing transition metal oxide, a sodium-containing phosphate compound, and a sodium-containing transition metal oxide.
[0317] For example, the general formula of the olivine-type phosphate active material (lithium-containing phosphate compound) is: Li x A y Me a M b P 1-c X c Y z , wherein 0≤x≤1.3, 0≤y≤1.3, and 0.9≤x+y≤1.3; 0.9≤a≤1.5, 0≤b≤0.5, and 0.9≤a+b≤1.5; 0≤c≤0.5; 3≤z≤5; A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of S, Si, Cl, B, C, and N; and Y includes one or more of O and F. Specifically, the olivine-type phosphate active material includes one or more of LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.
[0318] For example, lithium transition metal oxides (layered materials such as ternary, lithium nickelate / sodium, lithium cobaltate / sodium, lithium manganate / sodium, lithium-rich layered and rock salt phase layered materials). The general formula of the layered structure positive electrode active material is: Li x A y Ni a Co b Mn c M (1-a-b-c) Y z , wherein 0≤x≤2.1, 0≤y≤2.1, and 0.9≤x+y≤2.1; 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0.1≤a+b+c≤1; 1.8≤z≤3.5; A includes one or more of Na, K, and Mg; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; Y includes one or more of O and F. Optionally, y=0. Specifically, the layered structure positive electrode active material may include lithium cobalt oxide LCO, lithium nickel oxide LNO, lithium manganese oxide LMO, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333),LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622),LiNi 0.8 Co 0.1 Mn 0.1 One or more of O2 (NCM811) and NCA.
[0319] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil or an aluminum alloy foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include a combination of one or more selected from aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. The polymer material base layer may include a combination of one or more selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0320] In some embodiments, the positive electrode active material layer may further optionally include a positive electrode conductive agent. The present application does not particularly limit the type of positive electrode conductive agent. For example, the positive electrode conductive agent may include a combination of one or more selected from superconducting carbon, conductive carbon black, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the positive electrode conductive agent is less than 5% based on the total mass of the positive electrode active material layer.
[0321] In some embodiments, the positive electrode active material layer may also optionally include a positive electrode binder. The embodiments of the present application do not particularly limit the type of positive electrode binder. As an example, the positive electrode binder may include a combination of one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin. In some embodiments, based on the total mass of the positive electrode active material layer, the mass percentage of the positive electrode binder is less than 5%. Compared to the crystallinity of the fluoropolymer of the embodiment of the present application, the crystallinity of the positive electrode binder is higher. Compared to the melting temperature of the fluoropolymer of the embodiment of the present application, the melting temperature of the positive electrode binder is higher.
[0322] The positive electrode active material layer is typically formed by coating a positive electrode slurry onto a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is typically formed by dispersing the positive electrode active material, a liquid-absorbing polymer, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent can be, but is not limited to, N-methylpyrrolidone (NMP). Of course, the preparation of the positive electrode sheet is not limited to the above method; the preparation methods described above can also be used.
[0323] [Negative electrode]
[0324] The battery cell includes a negative electrode plate.
[0325] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. For example, the negative electrode current collector has two surfaces that are opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposing surfaces of the negative electrode current collector.
[0326] In some embodiments, the negative electrode film layer includes a negative electrode active material and a liquid-absorbing polymer.
[0327] As some examples, the negative electrode film layer includes a polymer layer containing a liquid-absorbing polymer and a negative electrode active material layer containing negative electrode active material particles, wherein the negative electrode active material layer is disposed on at least one surface of the negative electrode current collector.
[0328] The polymer layer is disposed on a surface of the negative electrode active material layer facing away from the negative electrode current collector.
[0329] As some other examples, there are a plurality of negative electrode active material particles, a gap exists between two adjacent negative electrode active material particles, and the liquid-absorbing polymer is distributed in the gap.
[0330] In some embodiments, the negative electrode film layer may further include a liquid-retaining polymer.
[0331] In some embodiments, 3.00≤v / λ<50.00. For example, v / λ can be 3.00, 3.20, 3.40, 3.50, 4.00, 4.50, 5.00, 5.50, 6.00, 6.50, 7.00, 8.00, 9.00, 9.50, 10.00, 10.50, 11.00, 12.00, 13.00, 14.00, 15.00, 20.00, 25.00, 28.00, 30.00, 35.00, 40.00, 45.00, 50.00, or a range consisting of any two of the foregoing values.
[0332] In some embodiments, the mass percentage of the liquid-absorbing polymer is 0.2% to 5.0% based on the mass of the negative electrode active material layer. When the mass percentage of the liquid-absorbing polymer is within the above range, the liquid-absorbing capacity of the negative electrode active material layer can be significantly improved. For example, the mass percentage of the liquid-absorbing polymer B% can be 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, or a range consisting of any two of the above values.
[0333] The negative electrode active material can be any negative electrode active material known in the art for use in battery cells. For example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, a silicon-carbon composite, a silicon-nitrogen composite, and a silicon alloy. The tin-based material may include at least one of elemental tin, tin oxide, and a tin alloy.
[0334] In some embodiments, the negative electrode active material layer may further optionally include a negative electrode conductive agent. The present embodiments do not particularly limit the type of the negative electrode conductive agent. For example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the negative electrode conductive agent is ≤5% based on the total mass of the negative electrode active material layer.
[0335] In some embodiments, the negative electrode active material layer may further optionally include a negative electrode binder. The present application embodiment does not particularly limit the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage of the negative electrode binder based on the total mass of the negative electrode active material layer is ≤5%.
[0336] In some embodiments, the negative electrode active material layer may optionally include other additives. For example, these additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, and the like. In some embodiments, the weight percentage of these other additives is ≤ 2% based on the total weight of the negative electrode active material layer.
[0337] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, a copper alloy, nickel, a nickel alloy, titanium, a titanium alloy, silver, and a silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0338] The negative electrode active material layer is typically formed by coating a negative electrode slurry onto a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is typically formed by dispersing the negative electrode active material, a liquid-absorbing polymer, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring them uniformly. The solvent can be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water. Of course, the preparation of the negative electrode sheet is not limited to the above method; the preparation methods described above may also be used.
[0339] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode active material layer. For example, in some embodiments, the negative electrode plate described herein further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode active material layer and disposed on the surface of the negative electrode current collector. In other embodiments, the negative electrode plate described herein further includes a protective layer covering the surface of the negative electrode active material layer.
[0340] [Electrolytes]
[0341] During the charge and discharge process of a battery cell, active ions are embedded and released back and forth between the positive and negative electrodes, and the electrolyte conducts the active ions between the positive and negative electrodes. This application does not specifically limit the type of electrolyte, and it can be selected according to actual needs.
[0342] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not particularly limited and can be selected according to actual needs.
[0343] When the battery cell of the present application is a lithium-ion battery, as an example, the electrolyte salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0344] When the battery cell of the present application is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).
[0345] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), diethyl sulfone (ESE), tetrahydrofuran THF, 2-methyltetrahydrofuran 2me-thf, 1,3-dioxolane DOL, dimethoxymethane DMM, 1,2-dimethoxyethane DME, and diethylene glycol dimethyl ether DG.
[0346] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.
[0347] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly through a winding process and / or a lamination process.
[0348] In some embodiments, the battery cell may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0349] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0350] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process or a lamination process.
[0351] The present application has no particular limitation on the shape of the battery cell, which can be cylindrical, square or any other shape. FIG1 shows a battery cell 5 with a square structure as an example.
[0352] In some embodiments, as shown in Figures 1 and 2, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.
[0353] The manufacturing method of the battery cell of the present application is well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, separator, and negative electrode sheet can be wound or laminated to form an electrode assembly. The electrode assembly is then placed in an outer packaging, dried, and then injected with electrolyte. The battery cell is then vacuum packaged, allowed to stand, formed, and shaped to obtain a battery cell.
[0354] In some embodiments of the present application, the battery cells according to the present application can be assembled into a battery module. The battery module can contain multiple battery cells, and the specific number can be adjusted according to the application and capacity of the battery module.
[0355] Figure 3 is a schematic diagram of an exemplary battery module 4. As shown in Figure 3 , within the battery module 4, multiple battery cells 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple battery cells 5 may be secured together using fasteners.
[0356] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of battery cells 5 are accommodated in the accommodation space.
[0357] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0358] Both the battery module 4 and the battery pack can be used as specific examples of batteries in the embodiments of the present application.
[0359] Figures 4 and 5 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 4 and 5, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 covers the lower case 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0360] Electrical devices
[0361] In a third aspect, the present application provides an electrical device, which includes at least one of the battery cells, battery modules, and battery packs of the present application. The battery cells, battery modules, and battery packs can be used as power sources for the electrical device, or as energy storage units for the electrical device. The electrical device may be, but is not limited to, a mobile device (such as a mobile phone, laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc. In some embodiments, the battery cell includes an injection hole for injecting electrolyte; when the battery cell is used in the electrical device, the injection hole is located at the bottom of the battery cell in the vertical direction. Since the amount of free electrolyte in the battery cell is extremely small, or even non-existent, arranging the injection hole at the bottom of the battery cell in the vertical direction can also improve the reliability of the battery cell, thereby improving the reliability of the electrical device.
[0362] The electric device can select a battery cell, battery module or battery pack according to its usage requirements. Figure 6 is a schematic diagram of an electric device as an example. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the electric device, a battery pack 1 or a battery module can be used. As another example, the electric device can be a mobile phone, a tablet computer, a laptop computer, etc. The electric device usually requires to be lightweight and thin, and a battery cell can be used as a power source.
[0363] Example
[0364] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0365] Example 1 Preparation of lithium-ion battery
[0366] (1) Preparation of positive electrode sheet:
[0367] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.
[0368] The liquid-absorbing polymer and the positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2O2 (NCM622), conductive carbon black, and binder polyvinylidene fluoride (PVDF) are thoroughly stirred in an appropriate amount of N-methylpyrrolidone (NMP) to create a positive electrode slurry. The mass ratio of liquid-absorbing polymer, NCM622, conductive carbon black, and PVDF in the positive electrode slurry is 0:97.5:1.4:1.1. The positive electrode slurry is coated onto a current collector aluminum foil and vacuum-dried at 100°C before cold pressing. The sheet is then trimmed, cut, and slit, and then dried at 85°C under vacuum for 4 hours to form the positive electrode sheet.
[0369] (2) Preparation of negative electrode sheet:
[0370] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.
[0371] The liquid-absorbing polymer, artificial graphite (the negative electrode active material), carbon black (the conductive agent), styrene-butadiene rubber (SBR) (the binder), and sodium carboxymethyl cellulose (CMC) (the thickener) were mixed uniformly in a weight ratio of 1.5:95.9:2:0.5:0.1 and added to deionized water to prepare the negative electrode slurry. The negative electrode slurry was coated on the current collector copper foil and dried at 85°C. After cold pressing, trimming, cutting, and slitting, the negative electrode sheet was dried at 120°C under vacuum for 12 hours.
[0372] (3) Preparation of electrolyte:
[0373] In an environment with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate are mixed in a volume ratio of 1:1:1 to obtain an electrolyte solvent, and then the lithium salt LiPF6 is mixed with the mixed solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0374] (4) Preparation of isolation membrane
[0375] A 7 μm polyethylene film (PE) was used as the substrate.
[0376] The liquid-retaining polymer is dispersed in dimethyl carbonate (DMC) solvent to form a mixed system, and the mixed system is sprayed onto both surfaces of the polyethylene film to form polymer layers. The atomizing solvent is water, and the mass content of the mixed system is 1%.
[0377] (5) Preparation of lithium-ion batteries:
[0378] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive electrode sheet and the negative electrode sheet to serve as an isolation, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, dried, and then injected with electrolyte, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0379] Comparative Example 1
[0380] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the positive electrode sheet, negative electrode sheet, and separator of Comparative Example 1 were all different from those of Example 1. The separator of Comparative Example 1 was a 7 μm polyethylene film (PE).
[0381] The preparation of the positive electrode is as follows:
[0382] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.
[0383] The positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), conductive carbon black, and binder polyvinylidene fluoride (PVDF) are thoroughly stirred in an appropriate amount of N-methylpyrrolidone (NMP) to create a positive electrode slurry. The mass ratio of NCM622, conductive carbon black, and PVDF in the positive electrode slurry is 97.5:1.4:1. The positive electrode slurry is coated on a current collector aluminum foil and vacuum-dried at 100°C before cold pressing. The sheet is then trimmed, cut, and slit, and then dried at 85°C under vacuum for 4 hours to form the positive electrode sheet.
[0384] Preparation of negative electrode sheet:
[0385] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.
[0386] The negative electrode active material, artificial graphite, the conductive agent, carbon black, the binder, styrene-butadiene rubber (SBR), and the thickener, sodium carboxymethyl cellulose (CMC), were mixed uniformly in a weight ratio of 97.4:2:0.5:0.1 and added to deionized water to form the negative electrode slurry. The negative electrode slurry was coated on the current collector copper foil and dried at 85°C. The negative electrode sheet was then cold-pressed, trimmed, cut, and slit, and then dried at 120°C under vacuum for 12 hours.
[0387] Comparative Example 2
[0388] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the material of the liquid-retaining polymer of the isolation membrane in Comparative Example 2 was changed, and the material of the liquid-absorbing polymer in the positive and negative electrode sheets was changed.
[0389] Example 1-2 to Example 1-10
[0390] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the content of the liquid-absorbing polymer in the positive and negative electrode sheets in Examples 1-2 to 1-10 was adjusted.
[0391] Example 2-1 to Example 2-6
[0392] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the type of at least one of the liquid-retaining polymer and the liquid-absorbing polymer was adjusted in Examples 2-1 to 2-6.
[0393] Example 3-1 to Example 3-5
[0394] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the coating weight of the liquid-retaining polymer in the separator was adjusted in Examples 3-1 to 3-5.
[0395] Example 4-1
[0396] A lithium-ion battery was prepared using a method similar to that of Example 1. Unlike Example 1, Example 4-1 adjusted the position of the polymer layer of the separator. Specifically, the steps of preparing the separator included:
[0397] 7μm polyethylene film (PE) was used as the separator substrate;
[0398] The silicon oxide particles and the binder aqueous solution type polyacrylic acid were mixed uniformly in an appropriate amount of solvent deionized water at a mass ratio of 20:80 to obtain a coating slurry.
[0399] The prepared coating slurry was applied on both surfaces of a PE substrate using a coater to form a heat-resistant coating.
[0400] The liquid-retaining polymer and the binder are dispersed in dimethyl carbonate (DMC) solvent to form a mixed system, and the mixed system is atomized and sprayed on the surface of the heat-resistant coating to form a polymer layer, thereby obtaining a separator.
[0401] Example 4-2
[0402] A lithium-ion battery was prepared using a method similar to that of Example 1. Unlike Example 1, Example 4-2 adjusted the preparation method of the isolation membrane. Specifically, the steps of preparing the isolation membrane included:
[0403] 7μm polyethylene film (PE) was used as the separator substrate;
[0404] The liquid-retaining polymer, the silicon oxide particles, and the binder aqueous solution type polyacrylic acid are mixed uniformly in a suitable amount of deionized water as a solvent at a mass ratio of 80:20 to obtain a coating slurry. The mass ratio of the liquid-retaining polymer to the silicon oxide particles is 1.5:1.
[0405] The prepared coating slurry was applied on both surfaces of a PE substrate using a coater to form a heat-resistant coating.
[0406] The liquid-retaining polymer and the binder are dispersed in dimethyl carbonate (DMC) solvent to form a mixed system, and the mixed system is atomized and sprayed on the surface of the heat-resistant coating to form a polymer layer, thereby obtaining a separator.
[0407] The data of the examples and comparative examples are shown in Table 1.
[0408] Test section
[0409] 1. Wetting properties of electrodes and separators in lithium-ion batteries
[0410] Take the negative electrode plate + separator structure after hot pressing at 80℃, with a structure width of 2.0cm and a height of 10cm; place the structure vertically in the electrolyte (with the plate height in the electrolyte being 1mm), record the height of the electrolyte rising after 2 minutes, and record the liquid rising height / time to characterize the liquid absorption rate of the negative electrode plate + separator overall structure.
[0411] Take the positive electrode plate + separator structure after hot pressing at 80°C, with a structure width of 2.0 cm and a height of 10 cm; place the structure vertically in the electrolyte (, with the plate height in the electrolyte being 1 mm), record the height of the electrolyte rising after 2 minutes, and record the liquid rising height / time to characterize the liquid absorption rate of the positive electrode plate + separator overall structure.
[0412] 2. Cycling performance of lithium-ion batteries at 5C
[0413] At 25°C, charge the lithium-ion battery at a 5C rate and discharge at a 1C rate. Calculate the capacity retention after 200 cycles, taking the initial discharge capacity as 100%. Capacity retention after 200 cycles (%) = 200th cycle discharge capacity / initial discharge capacity × 100%.
[0414] Test results
[0415] The test results are shown in Table 1 and Table 2.
[0416] Table 1
[0417] In Table 1, 60% methyl methacrylate means that the molar percentage of methyl methacrylate is 60% based on the total molar amount of methyl methacrylate, butyl acrylate and acrylonitrile.
[0418] In Table 1, the liquid retention capacity
[0419] The liquid retention rate (before pressurization) is (m1-M) / M×100%.
[0420] The liquid retention rate (after pressurization) is (m2-M) / M×100%.
[0421] Table 2
[0422]
[0423] In Table 2, 75% VDF means that the molar percentage of vinylidene fluoride VDF is 75% based on the total molar amount of vinylidene fluoride VDF, hexafluoropropylene HFP and ethylene.
[0424] Table 3
[0425] In Table 3, the porosity of the positive electrode film layer in the positive electrode sheets of the embodiments and comparative examples is 30.1%, and the porosity of the negative electrode film layer in the negative electrode sheets is 44.2%.
[0426] In Table 3, the ratio of the unit volume mass of the liquid-absorbing polymer in the electrode to the unit volume mass of the liquid-retaining polymer in the isolation membrane refers to the ratio of the sum of the monomer volume masses of the liquid-absorbing polymer in the positive electrode and the negative electrode to the unit volume mass of the liquid-retaining polymer in the isolation membrane.
[0427] In Comparative Example 1, the liquid-retaining polymer of the present application was not added to the separator, and the liquid-absorbing polymer was not added to the electrode, so the cycle performance of the battery cell was poor.
[0428] Although a polymer is added to the separator and the electrode in Comparative Example 2, the polymer has poor liquid retention and liquid absorption capabilities and cannot effectively improve the cycle performance of the lithium-ion battery.
[0429] Compared with Comparative Example 1, the embodiment of the present application is provided with a liquid-absorbing polymer in the electrode plate, which helps the electrode plate to absorb the electrolyte, so that the electrolyte infiltrates the electrode plate more evenly and fully, thereby improving the stability of the battery cell during the cycle; a liquid-retaining polymer is provided in the isolation membrane of the battery cell, and the isolation membrane has a strong liquid-retaining ability. During the cyclic charge and discharge process of the battery cell, the electrolyte is not easily squeezed out, thereby reducing the liquid shortage during the cyclic charge and discharge process, reducing battery polarization, and improving the cycle performance of the battery cell.
[0430] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and components may be substituted with equivalents without departing from the scope of the present application. In particular, the various technical features described in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but encompasses all technical solutions within the scope of the claims.
Claims
1. A battery cell, comprising an electrode assembly, wherein the electrode assembly comprises an electrode sheet and a separator; The electrode plate comprises a current collector and a film layer containing active material and liquid-absorbing polymer disposed on at least one surface of the current collector, and the electrode plate satisfies: v / λ≥1.2; v represents the liquid absorption rate of the film layer, and its unit is mg / s; λ represents the porosity of the membrane layer; The isolation film includes a liquid-retaining polymer, and the isolation film satisfies: M represents the mass of the separator that does not absorb the electrolyte, and its unit is g; m 1 It represents the mass of the isolation membrane weighed at ambient pressure after being immersed in the electrolyte for 2 hours, and its unit is g; m 2 It represents the mass of the isolation membrane weighed at a pressure of 10000N in ambient pressure after the isolation membrane is immersed in the electrolyte for 2 hours, and its unit is g.
2. The battery cell according to claim 1, in, The active material includes a positive electrode active material, The electrode plate satisfies: 1.2≤v / λ≤4.
50.
3. The battery cell according to claim 1 or 2, in, The active material includes a negative electrode active material, The electrode plate satisfies: 3≤v / λ<50.
00.
4. The battery cell according to any one of claims 1 to 3, in, The isolation film satisfies:
5. The battery cell according to any one of claims 1 to 4, in, The isolation film satisfies:
6. The battery cell according to any one of claims 1 to 5, in, The isolation film satisfies:
7. The battery cell according to any one of claims 1 to 6, in, The isolation film also includes a liquid-absorbing polymer; Optionally, The unit volume mass of the liquid-absorbing polymer in the electrode plate is A1, The unit volume mass of the liquid-absorbing polymer in the isolation membrane is A2, 1.0≤A1 / A2≤1.6; optionally, 1.2≤A1 / A2≤1.
5.
8. The battery cell according to any one of claims 1 to 7, in, The electrode plate also includes a liquid-retaining polymer; Optionally, The unit volume mass of the liquid-retaining polymer in the electrode plate is B1, The unit volume mass of the liquid-retaining polymer in the isolation membrane is B2, 0.4≤B1 / B2≤0.9; Optionally, 0.5≤B1 / B2≤0.
8.
9. The battery cell according to any one of claims 1 to 8, in, The unit volume mass of the liquid-absorbing polymer in the electrode plate is C1, the unit volume mass of the liquid-retaining polymer in the isolation membrane is C2, and 0.1≤C1 / C2≤5.
10. The battery cell according to any one of claims 1 to 9, in, The liquid-absorbing polymer includes at least one of an ether polymer and an ester polymer; Optionally, the liquid-absorbing polymer is made into a sheet-like structure; the sheet-like structure is m1 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency scanning test at +20)℃, and the slope of the elastic modulus G'-energy loss modulus G" curve was K 1 , 1<K 1 <∞,T m1 ℃ represents the melting temperature of the liquid-absorbing polymer; optionally, 1<K 1 ≤100; further optionally, 1<K 1 ≤10.
11. The battery cell according to claim 10, in, The ether polymer comprises at least one of the structural unit represented by formula (BI) and the structural unit represented by formula (BII), In formula (BI), R 21 and R 22 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; R 23 Including substituted or unsubstituted C1-C5 alkylene; In formula (BII), R 24 To R 27 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 alkoxy group or an ether group, and R 24 To R 27 At least one of them contains a substituted or unsubstituted C1-C3 alkoxy group or an ether group.
12. The battery cell according to claim 10 or 11, in, The ester polymer comprises at least one of the structural unit represented by formula (CI) and the structural unit represented by formula (CII), In formula (CI), R 31 , R 32 and R 33 Each independently includes a hydrogen atom, or a substituted or unsubstituted C1-C8 alkyl group; R 34 Including substituted or unsubstituted C1-C8 alkyl, or substituted or unsubstituted C1-C8 hydroxyalkyl; In formula (CII), R 35 including substituted or unsubstituted C2-C6 methylene; optionally, R 35 Each independently includes a substituted or unsubstituted C2-C4 methylene group.
13. The battery cell according to any one of claims 1 to 12, in, The liquid retaining polymer includes at least one of a fluorinated polymer and an aldehyde-ketone polymer; Optionally, the crystallinity of the fluorinated polymer measured by differential scanning calorimetry is Xc 2 , 0<Xc 2 ≤30%; the melting temperature of the fluorinated polymer is T m2 , its unit is ℃, 0<T m2 ≤140; Optionally, the aldehyde-ketone polymer is made into a sheet-like structure; the sheet-like structure is (T m3 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency scanning test at +20)℃, and the slope of the elastic modulus G'-energy loss modulus G" curve was K 3 , 0.8≤K 3 <∞,T m3 ℃ represents the melting temperature of the aldehyde-ketone polymer; Optionally, 0.8≤K 3 ≤100; further optionally, 0.8≤K 3 ≤10.
14. The battery cell according to claim 13, in, The crystallinity of the fluorinated polymer measured by differential scanning calorimetry is Xc 1 , 0<Xc 1 ≤30%; The melting temperature of the fluorinated polymer is T m1 , its unit is ℃, 0<T m1 ≤140; Further optionally, the glass transition temperature of the fluorinated polymer is T g1 , the unit is ℃, -150≤T g1 ≤60; Further optionally, the fluorinated polymer comprises at least one of the structural units represented by formula (AI) to the structural units represented by formula (AIII), In formula (AI) and formula (AII), R 11 , R 12 , R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 , R 12 , R 13 and R 14 At least one of them contains a fluorine atom; In formula (AIII), R 15 Including a single bond, a substituted or unsubstituted C1-C3 alkyl group; p is selected from a positive integer from 1 to 3; n is selected from a positive integer from 1000 to 30000.
15. The battery cell according to claim 13 or 14, in, The aldehyde-ketone polymer comprises at least one of the structural unit represented by formula (DI) and the structural unit represented by formula (DII), In formula (DI), R 41 Including single bonds, substituted or unsubstituted C1-C6 methylene; R 42 Including hydrogen atom, substituted or unsubstituted C1-C6 alkyl; In formula (DII), R 43 To R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from an integer from 0 to 5, and at least one of r and s is selected from a positive integer.
16. The battery cell according to any one of claims 1 to 15, in, The isolation membrane includes a porous substrate, and the liquid-retaining polymer is distributed in pores of the porous substrate.
17. The battery cell according to any one of claims 1 to 16, in, The isolation membrane includes a porous substrate and a polymer layer disposed on at least one surface of the porous substrate, wherein the polymer layer includes the liquid retaining polymer.
18. The battery cell according to any one of claims 1 to 17, in, The coating weight of the liquid retaining polymer is 0.5 mg / 1540.25 mm 2 Up to 5mg / 1540.25mm 2 .
19. A battery cell comprising the battery cell according to any one of claims 1 to 18.
20. An electrical device comprising the battery according to claim 19.
Citation Information
Patent Citations
Non-aqueous electrolyte secondary battery
CN105051961A
Isolation membrane and lithium ion secondary battery
CN106328865A
Pole piece and preparation method thereof
CN115832295A
Nonaqueous electrolyte secondary battery
JP2010092879A
Nonaqueous electrolyte secondary battery
JP2020035634A